1994
DOI: 10.1177/0032855594074002004
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection among New York State Female Inmates: Preliminary Results of a Voluntary Counseling and Testing Program

Abstract: New York State's prison population has the highest seroprevalence of human immunodeficiency virus (HIV) among incarcerated populations in the United States. Five percent of the State prison inmate population is female. To date there have been few studies of incarcerated females in New York State (NYS). Seroprevalence rates have ranged from 18.9% to as high as 29%. In 1991, counselors from the New York State Department of Health (NYSDOH) AIDS Institute's Criminal Justice Initiative, in collaboration with the St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…These findings are inconsistent with other studies of incarcerated men that have documented high rates of injection drug use (Grinstead et al, 2001(Grinstead et al, , 1997Lachance-McCullough, Tesoriero, Sorin, & Stern, 1994), and HCV infection (Hammett et al, 1999;Macalino et al, 2004;Solomon, Flynn, Muck, & Vertefeuille, 2004). Past research has found that most individuals who initiate drug injection do so in their late teens or early twenties (Carneiro, Fuller, Doherty, & Vlahov, 1999) and African Americans and Hispanics initiate drug injection at an older age than Caucasians (Battjes et al, 1992).…”
Section: Aids Care 239contrasting
confidence: 86%
“…These findings are inconsistent with other studies of incarcerated men that have documented high rates of injection drug use (Grinstead et al, 2001(Grinstead et al, , 1997Lachance-McCullough, Tesoriero, Sorin, & Stern, 1994), and HCV infection (Hammett et al, 1999;Macalino et al, 2004;Solomon, Flynn, Muck, & Vertefeuille, 2004). Past research has found that most individuals who initiate drug injection do so in their late teens or early twenties (Carneiro, Fuller, Doherty, & Vlahov, 1999) and African Americans and Hispanics initiate drug injection at an older age than Caucasians (Battjes et al, 1992).…”
Section: Aids Care 239contrasting
confidence: 86%
“…HIV prevalence tends to be lower among inmates who volunteer for HIV testing than among those who are tested through unlinked seroprevalence surveys (Behrendt et al, 1994; Hoxie et al, 1998; Lachance-McCullough, Tesoriero, Sorin, & Lee, 1993; Lachance-McCullough, Tesoriero, Sorin, & Stern, 1994). Consistent with this are data from a voluntary HIV testing program that took place in Men’s Central and Twin Tower’s jails during the same time period as our study and identified a much lower HIV prevalence than we did among both males (0.40%) and females (0.33%) (unpublished data; Office of AIDS Programs and Policy; 4/06).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the medically relevant special needs of seropositive female inmates, researchers have noted the increasing difficulties that HIV/AIDS infected women face in prison. For example, they must deal with social isolation, physical abuse, and the traumatic repercussions of stigmatization (Lachance-McCullough, Tesoriero, Sorin, & Stern, 1994;Olivero, 1992).…”
Section: Special Needs Of Women With Hiv/aidsmentioning
confidence: 99%